High-pressure behaviour of Prussian blue analogues: interplay of hydration, Jahn-Teller distortions and vacancies - Boström,HLB; Collings,IE; Cairns,AB; Romao,CP; Goodwin,AL (Dalton Transactions, 2019)
We report a high-pressure crystallographic study of four hydrated Prussian blue analogues: M[Pt(CN)6] and M[Co(CN)6]0.67 (M = Mn2+, Cu2+) in the range 0-3 GPa. Mn[Co(CN)6]0.67 was studied by single-crystal X-ray diffraction, whereas the other systems were only available in polycrystalline form. The Mn-containing compounds undergo pressure-induced phase transitions from Fm3[combining macron]m to R3[combining macron] at ∼1.0-1.5 GPa driven by cooperative tilting of the octahedral units. No phase transition was found for the orbitally disordered Cu[Co(CN)6]0.67 up to 3 GPa. Mn[Co(CN)6]0.67 is significantly softer than the other samples, with a bulk modulus of ∼14 GPa compared to ∼35 GPa of the powdered samples. The discrepant pressure responses are discussed in terms of the presence of structural defects, Jahn-Teller distortions, and hydration. The implications for the development of polar systems are reviewed based upon our high-pressure study.